Rice Tariffication Law: Education and Views of Farmers in the Southern Philippines - Jamil Nueva; Jenny Ann Tanaleon; Adonis Besa (ASEAN Journal of Science and Engineering Education, 2022)
The study was conducted to determine the views of farmers in the implementation of the rice tariffication policy. This qualitative study was conducted with 15 participants from the three barangays of the municipality of Norala South Cotabato, the Philippines using purposive sampling. On the awareness of farmers on rice tariffication law (RTL), it was found out that most of the farmers are aware of the implementation of RTL particularly through their access to social media such as radio and televisions, Facebook, and other online sources. On the views of farmers on RTL, it was found out that the majority of the farmers believe that their economic situations are being affected such as inflation, loss of profit, and failure of the harvest. On the issues encountered in the implementation of RTL, the following are found out: (1) continuous inflation rate in commodities and other basic needs, (2) high pricing fertilizer and pesticides, and (3) decrease in the yields of crop production.